Recovery Of Intra Parenchym Lesion Hemorragic Stroke - Dewi Nur Fiana (Fakultas Kedokteran, 2020)
Recovering from a stroke can be a lengthy process that requires patience, hard work, and commitment. It may take years to recover. Recovery time after a stroke is different for everyone—it can take weeks, months, or even years. Some people recover fully, but others have long-term or lifelong disabilities. Strokes can cause significant impairment in language, cognition, motor, and sensory skills. This is why it’s considered to be a leading cause of serious long-term disability. The hemorrhage at the left cortex and subcortex of temporal lobe gives manifestation to contralateral hemiparesis. In acute setting, we should optimize the cerebral blood oxygen perfusion, so the penumbra area can survive. After surviving the acute stage, we have to assest functional prognosis in activities and optimized it because patient still has the contralateral extremities to help with activities.Keywords: Functional ability, Hemorrhagic stroke, Rehabilitation,